Ekplorasi Bahan Ajar Geometri Dalam Kesinambungan Diskursus Matematika - Fitriawan, Dona (Pendidikan Matematika Universitas PGRI Yogyakarta, 2021)
This research is an exploration of the implementation of learning geometry mathematics through discourse and aims to get a model of theaching materials as adevelopment of those used by lecturers so far. The research was carried out through questionnaires, direct observation, and discussion of critical discourse analysis and was linked to important needs in mathematicals literacy. Exploration is constructed through theoretical reviews, synthesis from previous research, and examples of development though discourse. The contens of the questionnaire follow the natural discourse of the presentation of theacing materials on the dispotitions of lecturers and students. In particular, the exploration of theaching materials as part of the means of disseminating a culture of mathematics, an aesthetic description of mathematics, and dominant aspecs of lecturers and students. Development road maps are done through centralized examination of discourse, where data tajen from oral and written delivery and from texts that extend views on mathematics and by opening the choice of lectures and students. The result showed the depth of the description of teaching materials without the assumption that curriculum were sufficient to obtain the effectiveness of mathematical literacy and as a more contextual product.Keywords: theaching material, curriculum, continuity of the discourse of mathematics